Effect Of Return On Assets, Current Ratio And Net Profit Margin On Stock Price ( Studi Pada Perusahaan Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Tahun 2016 - 2019 ) - Desy Wulandani; M. Agus Salim; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to examine the effect of Return On Assets, Current Ratio and Net Profit Margin on stock prices in food and beverage companies listed on the Indonesia Stock Exchange in 2016-2019. The population used in this study were 26 food and beverage companies. The sample used as many as 12 food and beverage companies with a sampling technique using purposive sampling. The data analysis method used multiple linear regression analysis. The results of the study partially show that Return On Assets has no significant effect on stock prices, Current Ratio has a negative and significant effect on stock prices, Net Profit Margin has a positive and significant effect on stock prices. Simultaneously Return On Assets, Current Ratio and Net Profit Margin affect the stock price. Keywords: Return On Assets, Current Ratio, Net Profit Margin, Stock Price